Cost-effective reliability-based design optimization of base-isolated reinforced concrete building subject to stochastic ground motions - Shrestha, Subik; Peng, Yongbo (Structures (Oxford), 2025)
Mitigating seismic risks in high-intensity seismic areas remains a formidable challenge, particularly for traditional base-fixed structures due to economic and practical limitations. Base isolation systems offer a promising alternative, although they often exhibit intrinsic nonlinearities and confront uncertainties associated with ground motions. Designing base-isolated structures solely based on equivalent linearization techniques and limited station records may not ensure economy and safety. To this end, this study conducts a cost-effective reliability-based design optimization of base-isolated structures subject to non-stationary and non-Gaussian stochastic ground motions by utilizing the probability density evolution method (PDEM) and the non-dominated sorting genetic algorithm (NSGA-II). It aims at minimizing construction cost of base-isolated structures under targeted reliability constraints. For illustrative purposes, a ten-story two-bay planar reinforced concrete frame building with fixed and isolated bases is investigated. Numerical results demonstrate that the cost-effective reliability-based design optimization can effectively reduce seismic actions, leading to substantial cost savings and overall improved structural safety. Moreover, the presented method supports the informed decision-making. Furthermore, the optimal base-isolated building significantly outperforms the optimal elastic base-fixed structure in terms of both structural safety and construction cost.